Song of Songs. (Interpretation. A Bible commentary for teaching and preaching), Robert W. Jenson : book review - Mare, L. P. (Old Testament essays, 2006)
Extracted from text ... Jenson, Robert W 2005. Song of Songs. (Interpretation. A Bible commentary for teaching and preaching). Louisville, KY: John Knox. vi + 106 pages. Hardback with dust cover. US $24.95. ISBN 0-804-23117-6. Interpretation, a Bible commentary for teaching and preaching is one of my favourite commentary series. This volume on the Song of Songs completes this series. I have previously written reviews on a few of the volumes in the series (Leviticus, Joshua and Judges), and have wholeheartedly recommended them. Unfortunately, I cannot do the same for this volume. It really is a major disappointment. Jenson describes his interpretive strategy in ..